SAVDONI RAG’BATLANTIRISH: ASOSIY STRATEGIYALAR, METODLAR VA ULARNING SAMARADORLIGI - Kodirova Xurshida Ismoilovna, Kuranbayeva Dilnavo Madaminovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article analyzes the main strategies and methods of sales promotion, as well as their effectiveness. Sales promotion companies use various methods to promote their products and services in the market, attract consumers and increase their competitiveness. This work provides detailed information about the main forms of trade promotion, their role in practice, effectiveness and advanced methods.